نظام الأخلاق عند جلال الدين الرومي في كتابه المثنوي: دراسة تحليلية - فتحي بور، مريم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the virtues and moral vices of Jalaluddin al-Rumi by studying his book al-Mathnawi and the possibility of extracting a moral system through the study of the verses in poetry This study used qualitative research to collect and examine the details contained in the poems, analyse them, examine the 11 individual moral virtues and 11 moral vices and link the interpretations of the poetic texts in the areas mentioned based upon original texts. Additionally, a moral system was extracted and drew the desired conclusions. The results show that Jalaluddin al-Rumi considered revelation to be the only decent source of legislation and the source of all arts and sciences. He criticised partial intellect that it is not an instrument of certainty knowledge, and is exposed to error, ego and forgetfulness. He praised the total mind that is closely related to revelation, characterised it as universal intellect and considered it the main method of delivering human to perfection. The results show that human beings enjoy free will and that they are responsible for their own actions. Intention plays a significant role in attaining self-perfection, upon which the value of moral action is measured. The most important result was reached by examining the poetic verses of al-Rumi. A moral ladder or hierarchical shape of morality was identified in which a Salik (follower) begins his first step by strictly adhering to Shariah law, performing his duties and forbidding the unlawful. The individual moral virtues are vigilance, repentance, fear, hope, trust, patience, thanksgiving, satisfaction and the immortality after sacrificing oneself for the sake of God. The study recommends an analytical examination on how to achieve the ethical system derived from al-Mathnawi, incorporate it in spiritual educational programmes and how to transfer knowledge from the spirit of the educator to the spirit of the learner. Furthermore, it recommends more research and analysis on social moral qualities, extract an ethical system from them and compare them with the ethical system obtained by the current study.